Molecular Analysis of Type 1 Fimbriae Operon in E. coli Isolated from UTI - Duaa Al-Musawi (Journal of Global Pharma Technology, 2016)
One hundred E.coli isolates wascollected from urinary tract infections. Patients aged between 2 and 73 years, 66 females, 34 males. E. coli's commitment to urinary epithelial cells appears to be 100% in local isolates and the ability of bacteria to form biofilm was detected by using conjured-plate method and result showed that 96% of these isolated capable to form biofilm and only 4 isolates non-producer. Types1 fimbrial adhesions are encode by a fimgene clusters, include nine gene essential for the biosynthesis. ( FimB, Fim E, fim A , FimI, Fim C, FimD, FimF, FimG, FimH ) according to this study all the above mentioned genes were detection using PCR technique but there percentage were differ with (93% , 85% , 98%, 98% , 100% , 100% , 100% ,100% ,98%) respectively . the results indicated that isolates were negative for fim H gene may be negative for biofim formation this indicated the importance of type 1 fimbriae in biofilm formation.Keywords: Uropathogenic Escherichiacoli (UPEC); Bioflim, (PCR); Type1fimbriae.